2012
DOI: 10.1111/j.1467-8659.2012.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of an Interactive Time‐Series Visualization that Combines Quantitative Data with Qualitative Abstractions

Abstract: In many application areas, analysts have to make sense of large volumes of multivariate time-series data. Explorative analysis of this kind of data is often difficult and overwhelming at the level of raw data. Temporal data abstraction reduces data complexity by deriving qualitative statements that reflect domain-specific key characteristics. Visual representations of abstractions and raw data together with appropriate interaction methods can support analysts in making their data easier to understand. Such a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Two suitable candidates have been already introduced in Section 2: KNAVE-II [27] and STZ [6]. A comparative evaluation [4] has already shown that STZ is as efficient as KNAVE-II in terms of completion time and error rate, and is even better for more complex tasks. For this reason, we consider STZ as a more appropriate candidate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two suitable candidates have been already introduced in Section 2: KNAVE-II [27] and STZ [6]. A comparative evaluation [4] has already shown that STZ is as efficient as KNAVE-II in terms of completion time and error rate, and is even better for more complex tasks. For this reason, we consider STZ as a more appropriate candidate.…”
Section: Discussionmentioning
confidence: 98%
“…At the maximum height, the time series is visualized as a line plot with coloured annotations highlighting transitions between qualitative abstractions; at the minimum height, quantitative data disappear and qualitative abstractions are visualized as coloured rectangles. A comparative evaluation between this hybrid visualization, also known as SemanticTimeZoom (STZ), and KNAVE-II is presented in [4]. That user study, a task-based controlled experiment with 20 participants, revealed that STZ outperforms KNAVE-II in terms of task completion time, while there is no significant difference in terms of error rate.…”
Section: Related Workmentioning
confidence: 96%
“…VIE-VENT uses temporal abstractions adapted to the context and derives high level trend patterns [19]. Among systems that apply abstractions especially for visualization, are Knave-II [27] and Midgaard [4,5]. Midgaard combines patient observation and treatment (plan) data, offers mechanism for semantic zooming, including data abstraction mapped to color in the lowest level of detail.…”
Section: Related Workmentioning
confidence: 99%
“…STZ is a visualization method for qualitative abstractions and the associated quantitative time-oriented data. This interactive visualization technique, which is referred to as SemanticTimeZoom (STZ), is adopted from the Midgaard system [38,39]. While, in previous publications the qualitative abstractions were defined on basis of a single variable, typically based on severity ranges from domain knowledge, we can apply here the event data from our classification as common abstraction for all variables.…”
Section: The User Interfacementioning
confidence: 99%
“…The description is rated as Figure 11. The SemanticTimeZoom (STZ) adopted from Midgaard [38,39] can interactively combine numerical raw data with qualitative events.…”
Section: Expert Reviewmentioning
confidence: 99%